The performance of profit and loss sharing (PLS) products: Evidence from Indonesian Islamic Rural Banking (IRB) - Luqman Hakim Handoko; Firmansyah Firmansyah (STES Islamic Village, 2022)
The main difference between Islamic banking and conventional is the concept of profit and loss sharing (PLS). Supposedly, banks have to use dominantly this concept. Nevertheless, products based on PLS are less of attention for the bankers to generate profit. Otherwise, the product based on the Murabahah contract is the first choice for the banker for profit-making. Therefore, this research generally aims to examine the performance of Islamic rural banking products as a source of generating revenue. Especially to prove that profit and loss sharing is the best way to generate profit. VECM analysis will apply to identify the contribution of Islamic rural banking products to generate income. In evaluating of financing performance of Islamic banks, the data was collected from the central banks’ reports from 2009 to 2019. The result showed that in the long-run and short-run the PLS financing product (Mudharabah and Musyarakah) has a positive and significant effect on generating revenue. The study also revealed that the impulse response also showed that PLS gives a positive response and is stable in the long run. Furthermore, based on variance decomposition PLS has a bigger contribution to revenue.